A comparison of wrist isokinetic muscle strength in wheelchair table tennis and wheelchair basketball players - Akinoglu, B.; Kocahan, T.; Yildirim, N. Ü.; Soylu, Ç.; Apur, U.; Hasanoglu, A. (Orthopaedic Journal of Sports Medicine, 2017)
Aim:The aim of this study was to compare isokinetic muscle strength of wrist flexor and extensor muscles in paralympic athletes. Methods:This study was carried out with the participation of 9 (4 females and 5 males) wheelchair (WC) table tennis players aged 24+3 and 8 male WC basketball players aged 26+3, met the criteria and voluntarly participate in the study. Body weight, height, body mass index and dominant extremity of the study subjects were recorded. Isokinetic measurement were performed with Isomed 2000® device. Isokinetic testing protocol; before the test all players performed the wrist flexion and extension isokinetic test with the 5 repeating at 90º/sec as a warm-up and comprehending the test. Then, wrist flexion and extension concentric-concentric strength measurements were performed with the 5 repeating at 60º/sec and with the 15 repeating at 240º/sec with the angle between 50 degrees of wrist flexion and 60 degrees of wrist extension and peak torque, peak torque/kg values and flexion/extension ratios were recorded. Mann-Whitney U test was used to compare isokinetic muscle strength quantitative variables in athletes. Findings:Isokinetic muscle strength of wrist flexors and extensors was higher in both sides in WC table tennis players with 60º/sec speed (p<0,05). Isokinetic muscle strength of wrist flexors and extensors was higher in both sides in WC basketball players with 240º/sec speed (p<0,05). There was no significant difference statistically between the groups in isokinetic wrist flexion and extansion peak torque/kg ratio in all speeds (p>0,05). Wrist flexion/extension peak torque ratios were similar in both groups. When examining the athletes flexion/extension ratios, wrist extensor muscles were weaker than flexor muscles and flexor muscles were average twice stronger than extensor muscles in both sports. Results: We thought that imbalance of muscle strength in the wrist may have occurred because of the use of a WC and requiring the intensive wrist flexors in playing sports. In both groups wrist ekstansor muscles were found to be weaker than wrist flexors and flexor/extensor ratio was found to be imbalance. We believe that all athletes using WC such as WC table tennis and WC basketball players have a strenght imbalance in the muscle of the wrist and as a result, this situation will increase the possibility of injury. Therefore, our study showed that weakness of wrist extensors and imbalance of muscle stenght should be taken into account in WC athletes in athletic training and exercise programs.